Psychosocial justice for students in custody. (1st July 2019) - Corcoran, Tim; White, Julie; te Riele, Kitty; Baker, Alison; Moylan, Philippa
Abstract : Availability to quality education is significantly beneficial to the life prospects of young people. In particular, for young people caught up in the justice system, it is argued that involvement in education reduces risk of further criminality and improves a person's prospects for future community engagement. This paper overviews a recent study undertaken in the Australian state of Victoria. The study worked with project partner, Parkville College, the government school operating inside the state's two detention centres, to examine what supports and hinders education for students in custody. Amongst other purposes, education should be about the pursuit of justice and if accepted as an ontological opportunity, education can invite the pursuit of a particular kind of justice ‐ psychosocial justice. Subsequently, psychosocial theory applied to educational practice in youth detention is inextricably linked to issues concerning justice, both for how theory is invoked and ways in which practice is enacted. The paper first introduces the concept of psychosocial justice then hears from staff connected to Parkville College regarding issues and concerns related to their work. As shown, education for incarcerated young people, not just in Australia but internationally, is enhanced by contributions from psychosocial studies providing a means to pursuing justice informed by a politics of psychosocialism.